Mathematics Model of Diabetes Mellitus Illness without Genetic Factors with Treatment - Nurul Fitriyah; Muhammad Wakhid Musthofa; Pipit Pratiwi Rahayu (Kaunia: Integration and Interconnection Islam and Science Journal, 2021)
Diabetes Mellitus is a metabolic disorder characterized by an increase in glucose levels in the blood (hyperglycemia), which causes various chronic complications due to abnormalities in insulin secretion. Diabetes Mellitus is known as the Mother of Disease because it is the mother of various other diseases such as hypertension, heart disease, stroke and blindness. In this paper, what would be studied was a mathematical model of Diabetes Mellitus without genetic factors with treatment, the model used for the approach in this case was in the form of SEIIT. The analysis includes determining the model's equilibrium point, determining the basic reproduction number (R0) and analyzing the stability around the equilibrium point. Furthermore, numerical simulation using MAPLE was given based on the values of the related parameters in the mathematical model that describes the conditions in each subpopulation class.